Separator for electrochemical device and electrochemical device including said separator

By using composite materials of amorphous polymers and inorganic fillers to prepare separation membranes, the problem of polypropylene and polyethylene separation membranes being easily shrinkable or melted at high temperatures is solved, and a separation membrane with high insulation voltage and mechanical strength is achieved, which improves the safety and energy density of the battery.

JP2025503193AActive Publication Date: 2025-01-30LG CHEM LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024544507
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-26
Filing Date
2023-01-26
Publication Date
2025-01-30
Estimated Expiration
2043-01-26

AI Technical Summary

Technical Problem

Existing polypropylene and polyethylene separation membranes are prone to shrink or melt at high temperatures, resulting in an increase in the risk of short-circuiting of the positive and negative electrodes inside the battery, and thinning leads to a decrease in insulation characteristics and mechanical strength, affecting battery safety and energy density.

Method used

The separation membrane is prepared by a composite material containing amorphous polymer and inorganic filler. The separation membrane is made by immersion phase separation method to ensure high insulation voltage and mechanical strength. Amorphous polymers such as polyimide, polyamideimide, etc. are used to combine inorganic filler such as alumina to form a separation membrane with high thermal stability.

Benefits of technology

It improves the thermal stability and mechanical strength of the separation membrane, reduces the risk of short circuit, enhances the safety and insulation performance of the battery, and is suitable for high-energy-density batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503193000001_ABST
    Figure 2025503193000001_ABST
Patent Text Reader

Abstract

The present invention provides a separator for an electrochemical device, the separator comprising a polymeric porous support and an inorganic composite porous layer formed on at least one surface of the porous support, the inorganic composite porous layer comprising a binder polymer and an inorganic filler, the content of the inorganic filler being 30 to 200 parts by weight based on 100 parts by weight of the binder polymer, the binder polymer comprising a non-crystalline polymer having a glass transition temperature (Tg) of 180°C or more, and the separator for an electrochemical device having a dielectric breakdown voltage of 2 kV or more. The separator for an electrochemical device according to the present invention has improved voltage resistance characteristics of an electrochemical device, exhibits a high dielectric breakdown voltage, and reduces the rate of short circuit occurrence (hi-pot failure rate) even under high voltage conditions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for an electrochemical device, and an electrochemical device including the separator.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0011666, filed on January 26, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] Recently, interest in energy storage technology has been increasing. As the fields of application expand to include energy for mobile phones, camcorders, and laptops, as well as electric vehicles, efforts in research and development of electrochemical elements are gradually becoming more concrete. Among these, interest is being shown in the development of secondary batteries, which are energy storage devices that can be charged and discharged based on electrochemical principles. In addition, in the development of such batteries, research and development related to new electrode and battery designs has been conducted recently in order to improve the capacity density and specific energy.

[0004] Lithium-ion secondary batteries, in particular, are batteries that can be used repeatedly because lithium ions store and generate electricity by going back and forth between positive and negative electrodes. Lithium-ion secondary batteries are characterized by high voltage and energy density, long cycle life, excellent storage properties, and high output, and are therefore being applied in a wide range of fields, including portable IT devices, batteries for electric vehicles, and energy storage systems (ESS). Among these, the spread of electric vehicles is the main key to the growth of secondary batteries and is the main growth driver of the secondary battery market.

[0005] The four main components of such a secondary battery are a positive electrode, a negative electrode, an electrolyte, and a separator. Among these, the separator separates the two electrodes in the secondary battery, the positive electrode and the negative electrode, to prevent electrical shorting caused by physical contact, and provides a path through which ions can move between the two electrodes via the electrolyte held in the micropores, thereby providing ion conductivity.

[0006] Such separation membranes are made of microporous polymer film materials having the above-mentioned functions, and polyolefin-based separation membranes are particularly widely used. Representative polyolefin-based separation membranes include polyethylene (PE)-based and polypropylene (PP)-based polymer materials.

[0007] However, polyolefin-based separators have a problem of low heat resistance because they shrink or melt at high temperatures. To solve this problem, a method of improving heat resistance by coating the surface of the separator with inorganic particles and a binder polymer is widely used. However, when the battery becomes hot due to internal / external stimuli, there is still a high possibility that the positive and negative electrodes will come into contact with each other due to the shrinkage or melting of the separator, causing a short circuit, and therefore there is a demand for improved battery safety.

[0008] In addition, there is a high demand for thinner separators to increase the energy density of batteries, but thinner separators may not contain a sufficient amount of insulating material, resulting in poor insulating properties or poor mechanical strength. Thus, there is a demand for separators that have excellent insulating properties and high mechanical strength. Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a separator for an electrochemical device having excellent insulating properties and a reduced incidence of short circuiting, and an electrochemical device including the separator.

[0010] Another object of the present invention is to provide a method for producing a separator for an electrochemical device using a immersion phase separation method, which has excellent insulating properties and a reduced rate of short circuit occurrence.

[0011] It will be readily apparent to those skilled in the art that other objects and advantages of the present invention can be realized by the means or methods recited in the claims and combinations thereof. [Means for solving the problem]

[0012] The present inventors have found that the above-mentioned problems can be solved by the following separator for an electrochemical device, an electrochemical device having the separator, and a method for manufacturing the electrochemical device.

[0013] The first embodiment is A separator for an electrochemical element, comprising: The separation membrane comprises a polymeric porous support and an inorganic composite porous layer formed on at least one surface of the porous support, The inorganic composite porous layer contains a binder polymer and an inorganic filler, The binder polymer includes a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, The content of the inorganic filler is 30 to 200 parts by weight based on 100 parts by weight of the binder polymer; The present invention relates to a separator for electrochemical devices, the separator having a dielectric breakdown voltage of 2 kV or more.

[0014] The second embodiment is the same as the first embodiment, The present invention relates to a separator for electrochemical elements, the separator having a dielectric breakdown voltage of 2 kV or more and 6 kV or less.

[0015] The third embodiment is the first or second embodiment, The present invention relates to a separator for electrochemical elements, the separator having a dielectric breakdown strength of 4.5 kV / milliinch or more.

[0016] The fourth embodiment is any one of the first to third embodiments, The present invention relates to a separator for an electrochemical device, wherein the separator has a total thickness of 5 μm to 20 μm.

[0017] The fifth embodiment is any one of the first to fourth embodiments, The present invention relates to a separator for electrochemical elements, wherein the amorphous polymer having a glass transition temperature (Tg) of 180°C or higher comprises polyimide (PI), polyamideimide (PAI), polyetherimide (PEI), polyphenylsulfone (PPSU), polyethersulfone (PES), polysulfone (PSU), or two or more of these.

[0018] The sixth embodiment is any one of the first to fifth embodiments, The present invention relates to a separator for electrochemical devices, wherein the binder polymer is made of a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or higher.

[0019] The seventh embodiment is any one of the first to sixth embodiments, The content of the inorganic filler is 40 to 185 parts by weight based on 100 parts by weight of the binder polymer.

[0020] The eighth embodiment is any one of the first to seventh embodiments, The present invention relates to a separator for electrochemical devices, wherein the inorganic filler has an average particle size of 20 nm to 700 nm.

[0021] The ninth embodiment relates to an electrochemical device including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the separator is a separator for an electrochemical device according to any one of the first to eighth embodiments.

[0022] The tenth embodiment is the ninth embodiment, The electrochemical device is a lithium secondary battery.

[0023] The eleventh embodiment is a method for manufacturing a separator for an electrochemical device according to any one of the first to eighth embodiments, (S1) preparing a polymeric porous support; (S2) applying a slurry containing a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, an inorganic filler, and a solvent to at least one surface of the polymeric porous support; (S3) immersing the polymer porous support coated with the slurry in a composition containing a non-solvent for the amorphous polymer, and drying the composition to form an inorganic composite porous layer.

[0024] The twelfth embodiment is the eleventh embodiment, The present invention relates to a method for producing a separator for an electrochemical element, wherein the non-solvent comprises water, methanol, ethanol, propyl alcohol, butyl alcohol, butanediol, ethylene glycol, propylene glycol, tripropylene glycol, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, isopropyl alcohol, or two or more of these. Effect of the Invention

[0025] The separator for an electrochemical device according to an embodiment of the present invention has excellent heat resistance and mechanical strength, and can ensure a high dielectric breakdown voltage and a low occurrence of short circuits.

[0026] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to only the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0027] [Figure 1] 1 is a cross-sectional SEM image of the separation membrane according to Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The present invention will be described in detail below. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.

[0029] Throughout this specification, when a part "comprises" another component, it means that the part may further include the other component, not excluding the other component, unless otherwise specified.

[0030] In addition, the term "about" is used throughout this specification to mean a numerical value or close to a numerical value when given the inherent manufacturing and material tolerances, and is used to prevent unconscionable infringers from unfairly taking advantage of the contents of the disclosure in which precise or absolute numerical values ​​are recited to aid in the understanding of this application.

[0031] Throughout this specification, the phrase "A and / or B" means "A, B, or both."

[0032] According to an embodiment of the present invention, a separator for an electrochemical device is The porous support includes a polymeric porous support and an inorganic composite porous layer formed on at least one surface of the porous support, The inorganic composite porous layer contains a binder polymer and an inorganic filler, The binder polymer includes a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, The content of the inorganic filler is 30 to 200 parts by weight based on 100 parts by weight of the binder polymer; The separator has a dielectric breakdown voltage of 2 kV or more.

[0033] The separator according to an embodiment of the present invention has improved withstand voltage characteristics of a battery chemical device and exhibits a high dielectric breakdown voltage. In addition, the separator according to an embodiment of the present invention can prevent overdetection of defective separators during Hi-Pot testing, thereby improving the test yield. Since the Hi-Pot test is also related to the thickness of the separator, the thin membrane separator proposed in the present invention has the advantage of preventing overdetection of defective thin membrane separators.

[0034] The separator according to an embodiment of the present invention has a dielectric breakdown voltage of 2 kV or more. If the dielectric breakdown voltage is less than 2 kV, the dielectric breakdown voltage is similar to the physical properties of the polymeric porous support, resulting in an increased hipot failure rate and poor effectiveness in terms of voltage resistance. For example, the dielectric breakdown voltage may be 2 kV to 6 kV, or 3 kV to 6 kV.

[0035] In the present invention, the term "dielectric breakdown voltage" refers to the maximum voltage that an insulator can withstand, and when a voltage is applied to an insulator and gradually increased, the voltage at which the insulator loses its insulating properties and its conductivity increases at a high voltage exceeding a certain value.

[0036] The breakdown voltage can be measured by placing an insulator between metal plates and then passing a direct current through the insulator under a specified voltage boost condition. For example, the breakdown voltage can be measured with an AC / DC / IR hipot tester. The measurement target is placed between an aluminum jig and a copper jig, and the DC conditions are set to a current of 0.5 mA and a voltage boost of 100 V / s (up to 6 kV). The measurement is completed when a short circuit occurs as the voltage rises, and the voltage at that point can be defined as the breakdown voltage.

[0037] According to one embodiment of the present invention, the dielectric breakdown strength of the separator may be 4.5 kV / milliinch or more. Preferably, it may be in the range of 4.5 to 7 kV / milliinch or 4.8 to 7 kV / milliinch. When the dielectric breakdown strength satisfies the above range, it is advantageous in improving the hipot yield.

[0038] In the present invention, the dielectric breakdown strength can be calculated by dividing the dielectric breakdown voltage by the thickness of the sample, that is, by dividing the dielectric breakdown voltage by the thickness of the separator.

[0039] The thickness of the separator according to an embodiment of the present invention is not particularly limited, but may be in the range of 5 μm to 20 μm, and preferably in the range of 8 to 20 μm or 10 to 18 μm, in order to exhibit improved insulating properties and heat resistance stability.

[0040] According to an embodiment of the present invention, the polymeric porous support is not limited as long as it has a structure having pores, and may be a porous polymer substrate, specifically, a porous polymer film substrate or a porous polymer nonwoven fabric substrate.

[0041] The porous polymer film substrate may be a porous polymer film containing a polyolefin such as polyethylene or polypropylene, and such a polyolefin porous polymer film substrate exhibits a shutdown function at a temperature of, for example, 80 to 130°C.

[0042] In this case, the porous polymer film may be formed from a polyolefin polymer such as polyethylene (high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-molecular weight polyethylene, etc.), polypropylene, polybutylene, polypentene, etc., a mixture of two or more of these polymers, or a derivative thereof.

[0043] Representative examples of commercially available polyolefin porous polymer films that can be used as such polymeric porous supports include, but are not limited to, wet polyethylene systems (Asahi Kasei E-Materials, Toray, SK I.E. Technology, Shanghai Energy, Sinoma, Entek), dry polypropylene systems (Shenzhen Senior, Cangzhou Mingzhu), and dry polypropylene / polyethylene multilayer structures (Polypore, Ube).

[0044] In addition, the porous polymer film substrate may be manufactured by forming various polymers such as polyester in addition to polyolefin into a film shape. In addition, the porous polymer film substrate may be formed in a structure in which two or more film layers are laminated, and each film layer may be formed from the above-mentioned polymers such as polyolefin and polyester alone or a mixture of two or more of them.

[0045] In addition, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed from a polymer such as polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalate, etc., either alone or in combination, in addition to the above-mentioned polyolefin-based polymers.

[0046] The thickness of the polymeric porous support is not particularly limited, but may be 1 μm or more, 3 μm or more, 15 μm or less, or 10 μm or less. When the thickness of the polymeric porous support satisfies this range, the problem of acting as a resistance layer can be improved while maintaining mechanical properties.

[0047] The pore size and porosity of the polymeric porous support are not particularly limited, but the porosity may be in the range of 10 to 95%, and the pore size (diameter) may be in the range of 0.1 to 50 μm. When the pore size and porosity are in such ranges, the problem of acting as a resistance layer can be prevented and mechanical properties can be maintained. In addition, the polymeric porous support may be in the form of a fiber or membrane.

[0048] The inorganic composite porous layer is located on one surface of the polymeric porous support and includes a binder polymer and an inorganic filler.

[0049] In addition, the inorganic composite porous layer is one of the constituent layers of the separator, and serves as an isolating layer to prevent short circuits between the positive and negative electrodes, while preventing the polymer porous support from directly contacting lithium metal.

[0050] The porosity of the inorganic composite porous layer may be in the range of 5 to 95%, but is not limited thereto. The thickness of the inorganic composite porous layer may be 1 μm or more, 3 μm or more, 15 μm or less, or 10 μm or less. When the thickness of the inorganic composite porous layer satisfies this range, the heat resistance is improved to suppress the occurrence of a short circuit, a thinner separator is achieved, and excellent insulating properties are obtained.

[0051] In the inorganic composite porous layer, inorganic fillers are filled and bound to each other by the binder polymer in a state of contact with each other, so that an interstitial volume is formed between the inorganic fillers, and the interstitial volume between the inorganic fillers becomes an empty space to form a pore. That is, the binder polymer adheres the inorganic fillers so as to maintain the bound state between the inorganic fillers, for example, the binder polymer connects and fixes the inorganic fillers to each other. Also, the pores of the inorganic composite porous layer are pores formed when the interstitial volume between the inorganic fillers becomes an empty space, and are spaces limited by inorganic fillers that are substantially in contact with each other in a packed structure (closed packed or densely packed) by the inorganic fillers.

[0052] The inorganic filler serves to form micropores by allowing spaces to be formed between the inorganic fillers, and also serves as a kind of spacer that allows the physical shape to be maintained. Generally, the inorganic filler has physical properties that do not change even at high temperatures of 200°C or higher, so the organic / inorganic composite porous film formed has excellent heat resistance.

[0053] Therefore, in a lithium secondary battery including the separator, even if the polymer porous support ruptures inside the battery under harsh conditions due to internal or external factors such as high temperature, overcharging, or external impact, the inorganic composite porous layer can prevent both electrodes from being completely short-circuited. Even if a short circuit does occur, the short-circuited area can be prevented from expanding, thereby improving the safety of the battery.

[0054] The inorganic filler is not particularly limited as long as it is electrochemically stable. In other words, the inorganic filler that can be used in the present invention is a filler that can be used in the range of the operating voltage of the applied battery (for example, Li / Li + There is no particular limitation on the inorganic filler as long as it does not undergo oxidation and / or reduction reactions at a temperature of 0 to 5 V relative to the reference voltage. Examples of such inorganic fillers include alumina (Al 2 O 3 ), fumed alumina, aluminum hydroxide (Al(OH) 3 ), magnesium hydroxide (Mg(OH) 2 ), boehmite (AlOOH), or a mixture of two or more of these. 2 O 3 ) may be used.

[0055] The average particle size (D50) of the inorganic filler is preferably in the range of 20 nm to 700 nm in order to form an inorganic composite porous layer with a uniform thickness and a suitable porosity thereof. Specifically, it may be in the range of 100 nm to 500 nm. When the average particle size (D50) of the inorganic filler satisfies this range, the dispersibility of the slurry for the inorganic composite porous layer is maintained, making it easy to control the physical properties of the separator, and preventing problems such as a decrease in mechanical properties due to an excessive increase in the thickness of the separator or an internal short circuit during charging and discharging of the battery due to an excessive pore size. In addition, the packing density increases, contributing to the thermal shrinkage rate, and the particle size in the above range can exhibit excellent high heat resistance.

[0056] In the present invention, the average particle size (D50) of the inorganic filler is defined as the particle size based on 50% of the particle size distribution. In the present invention, the average particle size (D50) of the inorganic filler can be measured by, for example, observation with an electron microscope using a scanning electron microscope (SEM) or a field emission scanning electron microscope (FE-SEM), or by using a laser diffraction method. When measuring by the laser diffraction method, more specifically, the inorganic filler is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000), and is irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and the average particle size (D50) based on 50% of the particle size distribution in the measuring device can be calculated.

[0057] The inorganic filler may be a primary particle that is a single particle, or a secondary particle formed from an aggregate of primary particles.

[0058] The content of the inorganic filler is 30 to 200 parts by weight based on 100 parts by weight of the binder polymer. Specifically, the content of the inorganic filler may be 30 parts by weight or more, 40 parts by weight or more, 200 parts by weight or less, or 185 parts by weight or less based on 100 parts by weight of the binder polymer. When the content of the inorganic filler satisfies this range, not only can the heat resistance be improved, but also the problem of reduced pore size and porosity of the inorganic composite porous layer formed due to an excessive content of the binder polymer can be prevented, and the problem of reduced adhesion between inorganic materials due to a reduced content of the binder polymer, resulting in deterioration of peel resistance of the inorganic composite porous layer can be solved.

[0059] The binder polymer includes an amorphous polymer having a glass transition temperature (Tg) of 180° C. or more. Specifically, the first binder polymer may be an amorphous polymer having a glass transition temperature (Tg) of 180° C. to 350° C. For example, the amorphous binder polymer may be, but is not limited to, polyimide (PI), polyamideimide (PAI), polyetherimide (PEI), polyphenylsulfone (PPSU), polyethersulfone (PES), polysulfone (PSU), or a mixture of two or more of these. Specifically, the glass transition temperature of the amorphous binder polymer is about 250 to 340° C. for polyimide, about 280 to 290° C. for polyamideimide, about 217° C. for polyetherimide, about 222° C. for polyphenylsulfone, about 230° C. for polyethersulfone, and about 185° C. for polysulfone.

[0060] According to an embodiment of the present invention, the binder polymer may be a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more.

[0061] According to an embodiment of the present invention, a method for producing a separation membrane includes the steps of: (S1) preparing a polymeric porous support; (S2) applying a slurry containing a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, an inorganic filler, and a solvent to at least one surface of the polymeric porous support; (S3) The method may include a step of immersing the polymeric porous support coated with the slurry in a composition containing a non-solvent for the amorphous polymer, and drying the composition to form an inorganic composite porous layer.

[0062] When the inorganic filler is applied to the inorganic composite porous layer, the slurry may be prepared by dissolving the amorphous polymer in a solvent (which may be a dispersion medium for the inorganic filler), adding the inorganic filler, and dispersing the mixture. In this case, the inorganic filler may be added in a state of being crushed to an appropriate size, or the inorganic filler may be added to a solution of the amorphous polymer, and then crushed and dispersed using a ball mill method or the like.

[0063] The solvent may have a solubility index similar to that of the binder polymer and a low boiling point, which facilitates uniform mixing and subsequent solvent removal.

[0064] Examples of such a solvent may be one or a mixture of two or more compounds selected from acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, methanol, ethanol, isopropyl alcohol, and water.

[0065] In this case, the solvent may function as a solvent for dissolving the binder polymer or as a dispersion medium for dispersing the binder polymer, depending on the type of the binder polymer to be mixed.

[0066] According to an embodiment of the present invention, the method of coating the slurry on the polymeric porous support includes a pre-metering method and a post-metering method. The pre-metering method is a method in which a coating amount is determined in advance and introduced, such as slot die coating and gravure coating. The post-metering method is a method in which a sufficient amount of the slurry, which is a coating liquid, is applied to the polymeric porous support, and then a specified amount is scraped off, such as bar coating. There is also a direct-metering coating method that combines the pre-metering method and the post-metering method.

[0067] The slurry can be applied by a non-limiting method such as the method described above, and the polymeric porous support to which the slurry has been applied can be immersed in a composition containing a non-solvent to cause phase separation and form an inorganic composite porous layer.

[0068] According to one embodiment of the present invention, the non-solvent may be an aqueous solvent or an aqueous solvent mixed with an oil-based solvent. For example, the non-solvent may include water, methanol, ethanol, propyl alcohol, butyl alcohol, butanediol, ethylene glycol, propylene glycol, tripropylene glycol, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, isopropyl alcohol, or two or more of these. Specifically, the non-solvent may be water mixed with N-methyl-2-pyrrolidone or water mixed with dimethylacetamide.

[0069] The electrochemical device according to the embodiment of the present invention includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and the separator is the separator according to the embodiment of the present invention described above.

[0070] The electrode to be used with the separator of the present invention is not particularly limited, and may be prepared by bonding an electrode active material to an electrode current collector by a conventional method well known in the art.

[0071] Non-limiting examples of the positive electrode active material among the electrode active materials include conventional positive electrode active materials used in the positive electrodes of conventional lithium secondary batteries, and in particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide obtained by combining these materials.

[0072] Non-limiting examples of the negative electrode active material include conventional negative electrode active materials used in the negative electrodes of conventional lithium secondary batteries, and in particular, lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite, other carbons, and other lithium adsorbent materials are preferred.

[0073] Non-limiting examples of positive current collectors include foils made of aluminum, nickel, or combinations thereof, and non-limiting examples of negative current collectors include foils made of copper, gold, nickel, or copper alloys, or combinations thereof.

[0074] The electrolyte used in the electrochemical element according to one embodiment of the present invention is + B - and the like, + Li + , Na + , K + or a combination thereof, - PF 6 - , B.F. 4 - , Cl - , Br - , I - , ClO 4 - , AsF 6 - , C.H. 3 CO 2 - , C.F. 3 SO 3 - , N(CF 3 SO 2 ) 2 - , C(CF 2 SO 2 ) 3 -or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or a mixture thereof.

[0075] The electrolyte may be injected at an appropriate stage in the battery manufacturing process depending on the manufacturing process and desired physical properties of the final product, i.e., before battery assembly or at the final stage of battery assembly.

[0076] The present invention also provides a battery module including a battery having an electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool driven by an electric motor, electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like, electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters), electric golf carts, and power storage systems. EXAMPLES

[0077] The present invention will be described in detail below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.

[0078] The separation membranes of the examples and comparative examples were produced in the following manner.

[0079] <Example 1> Polyetherimide (PEI, weight average molecular weight: 128,000) was dissolved in N-methyl-2-pyrrolidone (NMP) as an organic solvent, and Al with an average particle size of 100 nm was added as an inorganic filler. 2 O 3 The amount of the inorganic filler was 40 parts by weight relative to 100 parts by weight of polyetherimide.

[0080] The prepared slurry was applied to one side of a polyethylene porous support (thickness 9 μm, porosity 45%), and then placed in a coagulation bath containing water for the NIPS process, followed by drying.

[0081] <Examples 2 to 5 and Comparative Examples 1 to 4> Separator membranes were prepared in the same manner as in Example 1, except that the contents of the binder polymer and inorganic filler were changed as shown in Table 1 below.

[0082] [Table 1]

[0083] <Evaluation of separation membrane properties> The physical properties of the separation membranes prepared in the Examples and Comparative Examples were evaluated by the following methods.

[0084] (1) Thickness of the separation membrane The thickness of the separation membrane was measured using a thickness gauge (Mitutoyo Corporation, VL-50S-B).

[0085] (2) Measurement of dielectric breakdown voltage The voltage was measured with an AC / DC / IR high-pot tester. The measurement target was placed between an aluminum jig and a copper jig, and the DC conditions were set to a current of 0.5 mA and a voltage rise of 100 V / s (up to 6 kV). The voltage at which a short circuit occurred as the voltage rose was measured as the dielectric breakdown voltage.

Claims

1. A separator for an electrochemical device, comprising: The separation membrane comprises a polymeric porous support and an inorganic composite porous layer formed on at least one surface of the porous support, The inorganic composite porous layer contains a binder polymer and an inorganic filler, The binder polymer includes a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, The content of the inorganic filler is 30 to 200 parts by weight based on 100 parts by weight of the binder polymer; The separator for electrochemical devices has a dielectric breakdown voltage of 2 kV or more.

2. 2. The separator for an electrochemical element according to claim 1, wherein the separator has a dielectric breakdown voltage of 2 kV or more and 6 kV or less.

3. 2. The separator for an electrochemical element according to claim 1, wherein the separator has a dielectric breakdown strength of 4.5 kV / milliinch or more.

4. 2. The separator for an electrochemical device according to claim 1, wherein the separator has a total thickness of 5 μm to 20 μm.

5. 2. The separator for electrochemical devices according to claim 1, wherein the amorphous polymer having a glass transition temperature (Tg) of 180° C. or higher comprises polyimide (PI), polyamideimide (PAI), polyetherimide (PEI), polyphenylsulfone (PPSU), polyethersulfone (PES), polysulfone (PSU), or two or more of these.

6. 2. The separator for an electrochemical device according to claim 1, wherein the binder polymer is a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or higher.

7. 2. The separator for an electrochemical device according to claim 1, wherein the content of the inorganic filler is 40 to 185 parts by weight based on 100 parts by weight of the binder polymer.

8. 2. The separator for electrochemical devices according to claim 1, wherein the inorganic filler has an average particle size of 20 nm to 700 nm.

9. 9. An electrochemical element comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the separator is the separator for electrochemical elements according to claim 1.

10. The electrochemical device according to claim 9 , wherein the electrochemical device is a lithium secondary battery.

11. A method for producing the separator for electrochemical elements according to claim 1, (S1) preparing a polymeric porous support; (S2) applying a slurry containing a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, an inorganic filler, and a solvent to at least one surface of the polymeric porous support; (S3) immersing the polymer porous support coated with the slurry in a composition containing a non-solvent for the amorphous polymer, and drying the composition to form an inorganic composite porous layer.

12. 12. The method for producing a separator for an electrochemical element according to claim 11, wherein the non-solvent comprises water, methanol, ethanol, propyl alcohol, butyl alcohol, butanediol, ethylene glycol, propylene glycol, tripropylene glycol, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, isopropyl alcohol, or two or more of these.

Citation Information

Patent Citations

  • Coating slurry material for separators and preparation method of material, lithium ion battery separator and preparation method thereof, and lithium ion battery

    CN109301134A

  • Multilayered porous membrane and its manufacturing method

    JP2007273443A

  • Separation membrane for electrochemical devices

    JP2016532240A

  • Separator for power storage device and method for manufacturing the same

    JP2017139117A

  • Polylactam coated separator membrane and related coating formulations for lithium ion secondary batteries

    JP2018500739A